What do core practices offer in preparing novice science teachers for equitable instruction?. Issue 4 (12th March 2019) - Kang, Hosun; Zinger, Doron
Abstract: This study explores the affordances and constraints of using the four core practices of ambitious science teaching (AST) as the main curriculum of science methods courses in preparing novice teachers for equitable instruction. Employing a longitudinal qualitative case study approach, this study follows three novice secondary science teachers' trajectories over 3 years, from their preparation to their second year of teaching. Participants were three White women who taught primarily Latinx, English learners, exceptional learners, and/or those who live in poverty. The contemporary vision of science learning promoted by the Next Generation Science Standards and critical race theory guide our analysis of novice teachers' instruction. Findings suggest that using AST practices as the main curriculum of science methods courses can help prepare novice teachers for equity if the approximation of these practices facilitates novices in problematizing their normalized views, expectations, and practices of disciplinary teaching and learning. The core practices are limited, however, in their ability to develop novice teachers' critical consciousness about racism and systemic inequity, which profoundly affects interactions with marginalized youth in classrooms.